Bisnis Kreatif Mengoptimalkan Bidang Musik Dalam Rangka Peningkatan Pendapatan Domestik Suatu Daerah & Negara - Nur Achmad; Muzakar Isa; Kussudyarsana (Jurnal Litbang Sukowati : Media Penelitian dan Pengembangan, 2025)
Abstract. This study examines the role of the creative economy in contributing to regional economic growth by synthesizing empirical findings from reputable national and international research. Utilizing a simplified Systematic Literature Review (SLR) approach, the analysis covers a 15-year period (2010–2025), focusing on scholarly works that link the creative and industrial economy to Gross Regional Domestic Product (GRDP). From an initial pool of 52 relevant publications, only 25 Scopus-indexed and 5 credible non-Scopus articles met the inclusion criteria for rigorous analysis. The review reveals that the creative economy holds substantial potential to enhance regional economic performance, especially in times of economic uncertainty. However, the magnitude and nature of its impact vary based on local policy frameworks, institutional readiness, and socioeconomic contexts. Supportive innovation ecosystems and well-aligned government policies are key enablers in maximizing the sector’s productivity and resilience. Furthermore, the findings underscore the global relevance of the creative economy, highlighting its adaptability across diverse regions and economic structures. Beyond synthesizing the current literature, this study identifies critical gaps and future research directions. These include examining how the creative economy can respond to emerging global challenges such as climate change, digital transformation, and economic inequality. The integration of advanced technologies to foster creativity and innovation also emerges as a strategic imperative for sustainable regional development.